Analisis Faktor-Faktor yang Berpengaruh terhadap Behavioural Intention to Use E-Wallet Bagi Generasi Z Indonesia - Muhammad Faizul Haqi; Budi Astuti (Jurnal Informatika Ekonomi Bisnis, 2024)
Cashless payments via digital systems in the current era are seen as a modern payment alternative in several countries, including Indonesia. The emergence of digitalization via the internet has accelerated globalization and payment systems from manual transactions to online transactions. That is why in this day the behavioral intention to use e-wallets is increasingly high among Gen Z in almost all regions of Indonesia. Gen Z was born in an era of technological progress, where their behavior is very dependent on internet technology. This research purposes to analyze the effect of performance expectancy, effort expectancy, social influence, facilitating conditions, perceived compatibility, and trust on behavioural intention to use e-wallet. Populations in this research are Gen Z in Indonesia. Sampling in this research using convenience sampling technique through a questionnaire method, and collected as many as 169 samples in accordance with the criteria. In this research using SPSS version 20 to process data. The results showed that effort expectancy, facilitating conditions, and perceived compatibility had a positive effect to behavioural intention to use e-wallet. While performance expectancy, and trust had not a positive effect to behavioural intention to use e-wallet. And social influence had not a negative effect to behavioural intention to use e-wallet.